Copper Amalgam Working Electrode for Voltammetric Analysis ojSe02 - Khelfa Pramesti, Muthia
Selenium is a heavy metal pollutant in aquatic enviromnent. Selenit is a form of inorganic selenium which is toxic to living things. Therefore, we need a sensitive method, which is able to selectively detect and detennine the concentration of selenit species. In this research, the performance optimization to determine the selenit species with a square wave stripping voltammetry technique using copper amalgam woking electrode (CuHg). Validation of this method was perfonned using optimum parameter of deposition potential (Eacc) of -450 mV and time of deposition (tacc) of 800 seconds when detennine selenite with square wave stripping voltammetiy technique. This method has a good precision with the standard deviation value (% RSD) of 4.89%. The linear calibration curve is shown in the range of 0.03-0.1 mM with R2 as 0.988 and range 0. 1-0. 7 mM with R2 as 0.995 and also the detection limit as 9 JlM. The standard selenite was measured with square wave stripping voltanunetiy technique with a recovery percentage as 96.67o/o±2.94. The same solution was tested with AAS with a recovery percentage as 96.35% ± 2.36. The statistical test using t test shows that both of these results do not have significant differences with 95% confidence limits.